2010
DOI: 10.1007/s11240-010-9829-y
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration from in vitro leaf tissues of Viburnum dentatum L

Abstract: Shoots were regenerated from in vitro leaf tissues of two genotypes of Viburnum dentatum, a popular shrub species for landscape use. Adventitious shoots were induced when leaf tissues were cultured on woody plant medium (WPM) supplemented with either benzyladenine (BA) or thidiazuron (TDZ). Effects of cytokinin concentration, indole-3-butyric acid (IBA), and dark treatment on shoot regeneration were investigated. Dark treatment for the first 4 weeks of leaf explants cultured in the regeneration medium signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…* Indole-3-butyric acid (IBA). ** Indole-3-acetic acid (IAA) and green ash, as well as other woody species using halfstrength MS basal medium (Dai et al 2011;van Sambeek et al 2001;Zhu and Wei 2010). Exogenous auxin had no significant effect on the number of lateral roots formed compared to the control, except for the treatment of 4.9 lM IBA plus 2.9 lM IAA.…”
Section: Rooting Of Adventitious Shootsmentioning
confidence: 99%
“…* Indole-3-butyric acid (IBA). ** Indole-3-acetic acid (IAA) and green ash, as well as other woody species using halfstrength MS basal medium (Dai et al 2011;van Sambeek et al 2001;Zhu and Wei 2010). Exogenous auxin had no significant effect on the number of lateral roots formed compared to the control, except for the treatment of 4.9 lM IBA plus 2.9 lM IAA.…”
Section: Rooting Of Adventitious Shootsmentioning
confidence: 99%
“…The factors involved for optimum growth of plant includes sterilization, pH and light temperature. As for example, pH is maintained at 5.8 throughout the plant tissue culture before being autoclaved [7]. Then, for growing temperature in the growth chamber is at 25°C [6].…”
Section: Introductionmentioning
confidence: 99%
“…The growth curve of Bacupari calli indicated slow growth. According to Dai et al (2011), woody species are challenging because they have long life cycles and little genetic information available. Thus, future studies should be useful to provide information about the slow growth observed.…”
Section: Growth Curve Determinationmentioning
confidence: 99%